2017
DOI: 10.1371/journal.pone.0186234
|View full text |Cite|
|
Sign up to set email alerts
|

Determination and production of antimicrobial compounds by Aspergillus clavatonanicus strain MJ31, an endophytic fungus from Mirabilis jalapa L. using UPLC-ESI-MS/MS and TD-GC-MS analysis

Abstract: Endophytic fungi associated with medicinal plants are reported as potent producers of diverse classes of secondary metabolites. In the present study, an endophytic fungi, Aspergillus clavatonanicus strain MJ31, exhibiting significant antimicrobial activity was isolated from roots of Mirabilis jalapa L., was identified by sequencing three nuclear genes i.e. internal transcribed spacers ribosomal RNA (ITS rRNA), 28S ribosomal RNA (28S rRNA) and translation elongation factor 1- alpha (EF 1α). Ethyl acetate extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 83 publications
2
30
0
2
Order By: Relevance
“…Tetracycline was used as a positive control, with IZDs ranging from 13 to 21 mm (Akinyemi 2017). Mishra et al (2017) observed that ethyl acetate extract of the endophytic fungus A. clavatonanicus (MJ31), isolated from roots of Mirabilis jalapa (Nyctaginaceae), displayed antibacterial potential against B. subtilis, M. luteus, and S. aureus, with MICs of 0.078, 0.156, and 0.312 mg ml −1 , respectively.…”
Section: Antibacterial Properties Of Crude Extractsmentioning
confidence: 99%
“…Tetracycline was used as a positive control, with IZDs ranging from 13 to 21 mm (Akinyemi 2017). Mishra et al (2017) observed that ethyl acetate extract of the endophytic fungus A. clavatonanicus (MJ31), isolated from roots of Mirabilis jalapa (Nyctaginaceae), displayed antibacterial potential against B. subtilis, M. luteus, and S. aureus, with MICs of 0.078, 0.156, and 0.312 mg ml −1 , respectively.…”
Section: Antibacterial Properties Of Crude Extractsmentioning
confidence: 99%
“…They can synthesise multiple metabolites, which allow them to adapt to the variety of environments they inhabit. Some of these primary and secondary metabolites have been commercially exploited; generating several Aspergillus -related products and patents including antibiotics, anti-tumoral and anti-fungal agents as well as other compounds with a medical application, such as the cholesterol-lowering drug lovastatin [5,6,7,8,9]. Additionally, Aspergilli strains are involved in many modern industrial processes including the production of hydrolytic enzymes (e.g., pectinases) [10] and bulk chemicals (e.g., citric acid) but have also been used for centuries in Asia for the production of fermented foods, such as sake, soy sauce and miso [11].…”
Section: Introductionmentioning
confidence: 99%
“…Primary ITS-4 and ITS-5 were used in PCR amplification (Liang et al 2012;Pansanit and Pripdeevech 2018). The PCR amplicon was sequenced and blasted by using National Center for Biotechnology Information (NCBI) (Mishra et al 2017). Fungal DNA with the highest similarity selected and grouped using ClustalW program (Hannula and Veen 2016) in txt, MSF, and PHYLIP formats (Felsenstein 1989).…”
Section: Identification Of Endophytic Fungimentioning
confidence: 99%